Phenolic Compounds Isolated from The Fern Chingia sakayensis (Zeiller) Holtt - Suyatno Suyatno; Sri Hidayati Syarief; Nurul Hidajati; Rinaningsih Rinaningsih; Motoo tori; Kuniyoshi Shimizu Shimizu (Jurnal ILMU DASAR, 2009)
Four known phenolic compounds namely kaemferol, matteucinol, farrerol, and matteucinol-7-O-β-D-glucoside were isolated for the first time from the fern Chingia sakayensis (Zeiller) Holtt’s. All substances were separated by chromatographic techniques, purified by recrystalization, elucidated on the basis of spectroscopic evidence and by comparation with those reported data in literature. These results were very important to study the phytochemicals of the other fern in Chingia genus based on the chemotaxonomic approach.